Pengawasan sebagai Upaya dalam Pencegahan Pembiayaan Murabahah Bermasalah - Siregar, Anri Akta Perdana; Rokan, Mustapa Khamal; Harianto, Budi (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to analyze the dominant factor of Monitoring (Monitoring) as an Effort in Preventing Problematic Cheap-Based Financing KCP BSI Medan Marelan. The method used is the quantitative method, using a sample of 10 employees, the X variable is 7B and 1S and the Y variable is the supervision of cheap financing, the data collection technique used is the Likert Scale angle with data analysis techniques using factor analysis Barlett's sphericity test and Kiser-Mayer-Olkin (KMO) and the test by interpreting factors (minimum factor loading 0.4) was carried out with IBM SPSS 27 for windows. The results obtained are 2 factors are formed for monitoring (monitoring) including primary factors and factor 2 is given the name of secondary factors; the most dominant factor is the primary factor which includes character; capital, capacity and economic conditions. It can be interpreted that in carrying out protection efforts in preventing low-cost problem financing at the BSI Marelan KCP prioritizing personal and social customer relationships, business economics and conditions or business trips carried out by clients.